"Entrada dos palmares e sossego dos Tapuias do Rio Grande": as guerras de conquista dos sertões das Capitanias do Norte do Estado do Brasil (1654-1716) - Silva, Tyego Franklim da (2023)
The second half of the 17th century in Portuguese America was marked by a warlike conjuncture whose main intention was the effective conquest of the most inland portions of the captaincies. After the expulsion of the Dutch, in 1654, the military agenda of the main institutions of governance turned to war mobilizations on two frontiers: the mocambos in the Palmares region, in the captaincy of Pernambuco; and the hinterlands of the captaincies of Rio Grande, Paraíba and Ceará, where the “barbarians” indigenous were an obstacle to the advance of colonization. Such conquest wars took place practically simultaneously, with expenditure of troops and resources for both fronts of conquest. It was not uncommon for subjects to act on both frontiers, alternately, aiming to achieve their personal interests, adding services to the Crown that could be converted into royal favors. This thesis aims to analyze the process of consolidation of the colonial region of the Northern Captaincies of the State of Brazil from the conquest wars of the hinterlands, namely: the Wars of Palmares and the so-called “War of the Barbarians”. The actions of individuals and institutions directly linked to the movements of conquest of territories will be taken as guiding the analyses, mainly seeking to understand what were their motivations and interventions in the conquest processes, in the interval that extends from 1654 to 1716. To this end, diverse document sets were consulted, such as the Overseas Historical Archive, the Historical Documents Collection of the National Library and the Conde dos Arcos Collection, which, through the serial and quantitative method, were crossed with previously known information of the two events studied, in order to in order to expand existing understanding of the details of the conquest wars.